ADMISSIBILITY OF NON-MUSLIMS EVIDENCE IN CASES INVOLVING MUSLIM PARTIES IN NIGERIA COURT: A CURSORY EXAMINATION OF QUR’AN CHAPTER 5 VERSE 106 - Imam, Aliyu Aliyu; Murtadha, Ahmad Olusola (Jurnal Syariah, 2023)
The interpretation of Qur’an chapter 5 Verse 106 created a lot of divergent opinions among the early Muslim jurists, especially as regards the admissibility of the evidence of non-Muslims (people of scriptures) in cases involving Muslim parties. While some jurists reject their evidence on the basis that the verse in contemplation has been abrogated, others accepted it in line with the letters and spirit of the Qur’an provision solely, that is, in cases of bequest, on a journey and where Muslims are not available. There is also another candid but liberal opinion that allows such evidence in all circumstances where necessity dictates for same. Does this classical discourse represent the same position of our present society, or is it possible to adopt any of the classical arguments to our current situation, especially in Nigerian society where Muslims and people of other faith (especially Christians) intermingled in several affairs of life? What then will be the situation of the evidence of people who do not qualify as ‘people of scriptures’? This piece, through doctrinal analysis, founds that the classical jurists have exhausted all possible argument and their positions (depending on the school) could be adopted depending on the circumstance of each society and the necessity of each transaction. It is concluded that Muslims should be wary and conscious of the company to keep so as not to forestall compliance with the dictate of Shari‘ah.